Improving Adolescents’ Knowledge of Stunting through Health Education Interventions - Ekasari, Ranti; Asriani; Asisa Haerani; Aswadi; Hasbi Ibrahim (Universitas Islam Negeri Alauddin Makassar, 2026)
Stunting is a manifestation of chronic undernutrition that occurs during critical periods of growth and development, beginning in early life. Adolescents play an important role in stunting prevention, as they represent future parents whose knowledge and awareness can influence child health outcomes. This study aimed to improve adolescents’ knowledge regarding stunting, its causes, and preventive measures as an early strategy to reduce stunting prevalence. A quantitative study design was employed using a pre-test and post-test approach. Health education sessions were delivered to adolescents in Tanetea Hamlet and Lembang Loe Hamlet, with knowledge levels measured before and after the intervention using the same questionnaire. The results demonstrated a statistically significant improvement in adolescents’ knowledge after the intervention (p = 0.016; p < 0.05), indicating a meaningful difference between pre- and post-education scores. These findings suggest that health education interventions are effective in increasing adolescents’ understanding of stunting. It is recommended that structured training programs on stunting prevention be continuously provided for adolescents. Additionally, strengthening adolescents’ communication skills may enable them to disseminate stunting-related information to peers, families, and the wider community, while regular evaluations should be conducted to assess knowledge improvement and behavioral change outcomes.